Determination of the optimal camera distance for cloud height measurements with two all-sky imagers. (February 2019) - Kuhn, P.; Nouri, B.; Wilbert, S.; Hanrieder, N.; Prahl, C.; Ramirez, L.; Zarzalejo, L.; Schmidt, T.; Schmidt, T.; Yasser, Z.; Heinemann, D.; Tzoumanikas, P.; et al.
Highlights: An in-field study and theoretical modeling is conducted to derive the optimal camera distance. The in-field study includes seven different camera distances on 93 days. Theoretical modeling identified the major parameters for the optimal distance. A step-by-step guideline to derive the optimal distance is provided. Abstract: All-sky imager based systems can be used to measure a number of cloud properties. Configurations consisting of two all-sky imagers can be used to derive cloud heights for weather stations, aviation and nowcasting of solar irradiance. One key question for such systems is the optimal distance between the all-sky imagers. This problem has not been studied conclusively in the literature. To the best of our knowledge, no previous in-field study of the optimal camera distance was performed. Also, comprehensive modeling is lacking. Here, we address this question with an in-field study on 93 days using 7 camera distances between 494 m and 2562 m and one specific cloud height estimation approach. We model the findings and draw conclusions for various configurations with different algorithmic methods and camera hardware. The camera distance is found to have a major impact on the accuracy of cloud height determinations. For the used 3 megapixel cameras, cloud heights up to 12, 000 m and the used algorithmic approaches, an optimal camera distance of approximately 1500 m is determined. Optimal camera distances can be reduced to less than 1000 m if higher camera resolutions (e.g. 6 megapixel) are deployed. A step-by-step guide to determine the optimal camera distance is provided.